2021
DOI: 10.32098/mltj.01.2021.06
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Patellar Tendon Mechanical Properties and Oxygenation Detection by Near Infrared Spectroscopy in Males

Abstract: Background. The purpose of this study was to determine the correlation between the patellar tendon mechanical properties and oxygenation in healthy men. Methods. In two subsequent sessions, eight (mean age ± SD: 27 ± 4) recreationally active, healthy males performed 4-sec isometric knee extensions of the dominant leg at 20-80% of maximal voluntary contraction (MVC), maintaining a knee joint angle of 90° of flexion. In the first session, B-mode ultrasonography was used to record tendon length, cross-sectional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Some studies have shown that hypoxia following circulation restriction can induce in ammation and apoptosis leading to fascial degeneration [5,16,22,24]. Hoheisel et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that hypoxia following circulation restriction can induce in ammation and apoptosis leading to fascial degeneration [5,16,22,24]. Hoheisel et al…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a decrease in blood ow with subsequent deoxygenation may be a trigger for fascial degeneration (e.g., stiffening, brosis, or thickening). In addition, hypoxia-related proteins are mediators of cell in ammation and apoptosis and cause a signi cant shift in collagen matrix and expression, which may also promote fascial degeneration [22]. On the other hand, fascial restrictions obviously decrease blood ow by vascular compression [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that tendinopathies are associated with new vascularization with swelling and pain [7].…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…Recent studies indicate that tendinopathies are associated with new vascularization with swelling and pain [7]. However, what seems like a paradox could, according to Järvinen [8], also represent persistent preceding hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Blood circulation in fascial tissue may play a critical role in maintaining the biomechanical, proprioceptive, and nociceptive function of the TLF [5,[22][23][24]. Therefore, a decrease in blood flow with subsequent deoxygenation may be a trigger for fascial degeneration (e.g., stiffening, fibrosis, or thickening).…”
Section: Introductionmentioning
confidence: 99%